Arranging food beautifully tray and steam table act - Mitchell, Susan E. (John Wiley, 1999)
"This unique guide equips you with a stunning array of practical and effective techniques for presenting hot and cold food attractively on trays, buffets, and steam table lines. Expertly blending art and skill, it shares countless ideas on how to use color, composition, texture, props, and garnishes to enhance the presentation of items from every part of the menu. Whether you work in a catering, deli, institutional, hospitality, or other foodservice setting, you'll delight in these simple suggestions that take minutes and cost pennies. Clear step-by-step instructions, plus dozens of how-to illustrations and photographs make the job easy, and taste panel - approved recipes show you exactly how to get started. From tasteful touches to bold thematic inspirations, you'll find a cornucopia of creative possibilities in Arranging Food Beautifully."--Jacket.